1980
DOI: 10.1901/jeab.1980.34-185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Multiple Fixed‐interval Fixed‐ratio Schedule Performances: Dynamic Interactions at Different Fixed‐ratio Values

Abstract: Key pecking by three pigeons was maintained under a multiple fixed-interval fixed-ratio schedule of food presentation. The fixed-interval value remained at 3 minutes, while the fixed-ratio size was increased systematically in 30-response increments from 30 to either 120 (two pigeons) or 150 (one pigeon). At least two lower fixed-ratio values were also redetermined. The effects of ethanol (.5 to 2.5 g/kg) were assessed at each of the different schedule parameters. Both overall and running response rates under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…The decreases observed in circularlights performance with alcohol in the present study are consistent with results from previous studies in which sedafives decreased rates on this device in normal and drug abuser populations (e.g., Griffiths et al 1983;Higgins and Stitzer 1986b) and are also consistent with the effects of alcohol in nonhumans responding under FR schedules (Katz and Barrett 1978;Barrett and Stanley 1980). Increases in response rate are sometimes observed under lower alcohol doses in the nonhuman studies, but were not observed using the circular-lights device in the present study.…”
Section: Discus$ionsupporting
confidence: 92%
“…The decreases observed in circularlights performance with alcohol in the present study are consistent with results from previous studies in which sedafives decreased rates on this device in normal and drug abuser populations (e.g., Griffiths et al 1983;Higgins and Stitzer 1986b) and are also consistent with the effects of alcohol in nonhumans responding under FR schedules (Katz and Barrett 1978;Barrett and Stanley 1980). Increases in response rate are sometimes observed under lower alcohol doses in the nonhuman studies, but were not observed using the circular-lights device in the present study.…”
Section: Discus$ionsupporting
confidence: 92%
“…Ksir and McKearney (1978) compared effects of the related compound, promazine, under a multiple FI FR schedule with drug effects obtained under a primed Fl FR schedule (Ferster & Skinner, 1957 Waller (1961) also noted changes in effects of chlorpromazine on FI performances when conditions during the FR component were manipulated. Barrett and Stanley (1980) demonstrated a comparable phenomenon with ethanol. In these earlier experiments, the effects of drugs on FI responding were modified by the FR response requirement.…”
Section: Discussionmentioning
confidence: 66%
“…In general, the behavioral performances and the pharmacological results under such multiple schedules are comparable with those observed when they are studied in isolation, although interactions between components of multiple schedules have been noted both behaviorally (Reynolds, 1961) and pharmacologically (Barrett and Stanley, 1980;Barrett et al, 1989). The second article in the series on Studies on Behavior examined the effects of pentobarbital, methamphetamine, and scopolamine on discriminative performances, again in pigeons (Dews, 1955b).…”
Section: Studies On Behavior II the Effects Of Pentobarbital Methamentioning
confidence: 92%